The importance of creatine supplementation in sports practice: A literature review (Research, Society and Development, 2024)
Considered an endogenous substance, creatine is synthesized by the body and can also be obtained through diet. It is widely used as a supplement, especially in sports, by individuals who engage in physical exercises and athletes. Creatine supplementation has proven effective in increasing muscle capacity and lean mass. Its ergogenic effect is attributed to the increase in phosphocreatine levels in muscles, which promotes energy regeneration during high-intensity physical activities and improves muscle endurance. The study results indicate that creatine supplementation is generally safe when consumed in appropriate doses and from quality products. However, its use should be guided by healthcare professionals. Combining creatine with carbohydrate sources has shown potential to optimize its absorption by increasing insulin levels, enhancing muscle nutrient uptake. Although the long-term effects of supplementation remain controversial, risks associated with excessive use, such as dehydration and muscle fatigue, warrant attention. Future studies should continue investigating the effects of creatine on physical performance and body composition, considering its various forms and dietary sources, as well as the potential adverse effects of indiscriminate use. Creatine supplementation can support muscle hypertrophy, energy metabolism during exercise, and post-exercise recovery, provided it is incorporated responsibly.